Assessing the Impact of the COVID-19 Pandemic: A Critical Analysis of the Indian Economy and Federal Structure (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The COVID-19 pandemic has been a once-in-a-generation crisis, profoundly impacting health, economic, and fiscal systems across the globe. In India, the pandemic tested the resilience of the country's federal structure, highlighting the critical role of local governments in crisis management and recovery. This study critically analyzes the economic and fiscal dimensions of the pandemic's impact on India, with a focus on the interplay between central, state, and local governments. Drawing on secondary data from sources such as the RBI, NITI Aayog, and WHO, the paper examines the pandemic's spatial and temporal spread, its economic repercussions, and the fiscal challenges faced by sub-national governments. The findings reveal that the pandemic exacerbated existing fiscal strains, particularly at the local level, while also underscoring the need for decentralized governance in crisis response. The study concludes with policy recommendations for strengthening India's federal structure and enhancing the financial resilience of local governments to better manage future crises.